Fecundidad de Cichlasoma dovii (Pisces: Cichlidae) en el embalse Arenal, Guanacaste, Costa Rica - Cabrera Peña, Jorge (Universidad de Costa Rica, 1992)
he fecundity of Cichlasoma dovii (Gunther, 1864) was studied in the Arenal Reservoir (Guanacaste, Costa Rica) from January 1985 through August 1987. Counts of ovules in ovaries of 750 gravid females (maturity stage IV and V) revealed lhat lhe relationship between total lenglh and number of ovules is F= 2307 + 282.2 (Lt - 25.15) (F= fecundity, Lt= total length).